Bone mineral content and bone mineral density in female swimmers during the time of peak bone mass attainment - Dlugolecka, B.; Czeczelewski, J.; Raczynska, B. (Biology of Sport, 2011)
The aim of this study was to assess bone mineral content and bone mineral density in girls practising swimming in the period of peak bone mass attainment in comparison to girls at the same age who are not actively involved in sports. This study involved girls from sports school specialising in swimming (n=41) aged 11-15 years, practising swimming (non-weight bearing activities), and girls at the same age not actively involved in sports (n=45). The current condition of bones was assessed based on the method of densitometry DEXA (lumbar spine L2-L4). Data on sports careers, including the length of training and training load, and hormonal status were collected using a diagnostic survey with an especially developed questionnaire. The quantitative composition of diet was determined based on 3 individual interviews on dietary intake in the last 24 hours preceding the test. Analysis of the results showed that the average values of the measured bone parameters were not different between the groups. However, we observed a trend of higher values in the control group. In the assessment of diet, we observed in both groups a deficiency in average calcium intake. Based on the results it can be concluded that the tested female swimmers were not at increased risk of developing osteopenia, when compared to girls not actively involved in sports.